Implementation insight for High Performance Messaging Solution - Natarajan, Muralidaran; Nandlal L, Sarda; Sharad C, Srivastava (International Journal of Computer Sciences and Engineering, 2015)
This paper addresses the messaging needs of decomposed multi-tier applications to support high performance. In the transformation exercise, the applications are getting decomposed into multiple logical tiers and get deployed in clusters to take advantage of computing power available in multi-core commodity hardware. In such deployments the communication between the tiers or layers within the deployment is critical for such transformations, as there are millions of small packets moving across these tiers and gets processed at different stages. It is important that a suitable messaging middleware is put to use for the success of such transformation exercise to address the transportation of messages across tiers. This study provides an insight to the developer community on, (a) various communication protocols current and emerging ones that can be used given a problem situation and the deployment nuances of these protocols (b) messaging models and middleware available for such deployment (c) key factors that are to be kept in mind for selection of such commercially available messaging middleware and (d) finally, approach towards deployment of such middleware and key parameters that are available for fine tuning to achieve the desired scalability and latency.